Belanja Daerah Program Sektor Pertanian dan Dana Desa terhadap Angka Kemiskinan melalui PDRB Sektor Pertanian - Prasetyo Yuli Usaid; Ahmad Yunani (Universitas Darwan Ali, 2021)
The rural poverty rate in South Kalimantan Province decreased in 2018 amidst the poverty rate between rural and urban areas is still relatively high. However, the high rate of urban population exceeding rural areas is followed by a higher poverty rate in rural areas than in cities. This research is a quantitative research using Partial Least Square (PLS) data analysis. This research was conducted in South Kalimantan Province. Election of South Kalimantan Province for the 2016-2017 period. The purpose of this study is to analyze how much influence the Agricultural Sector Regional Expenditures and Village Funds have on the agricultural sector GRDP, then the effect on its poverty rate. The results show that the Regional Expenditures for the Agricultural Sector Program and village funds do not significantly increase the GRDP of the Agricultural Sector. Regional Expenditures for the Agricultural Sector Program and village funds have a significant influence on the Poverty Rate. The GRDP of the Agricultural Sector has a significant influence on the Poverty Rate. Regional Expenditures for the Agricultural Sector Program through the GRDP of the Agricultural Sector and Village Funds do not have a significant effect on reducing the Poverty Rate inSouth Kalimantan.